2014
DOI: 10.1038/ncomms6715
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Kit signals on endolysosomes and endoplasmic reticulum are essential for neoplastic mast cell proliferation

Abstract: Kit is a receptor-type tyrosine kinase found on the plasma membrane. It can transform mast cells through activating mutations. Here, we show that a mutant Kit from neoplastic mast cells from mice, Kit(D814Y), is permanently active and allows cells to proliferate autonomously. It does so by activating two signalling pathways from different intracellular compartments. Mutant Kit from the cell surface accumulates on endolysosomes through clathrin-mediated endocytosis, which requires Kit’s kinase activity. Kit(D81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(88 citation statements)
references
References 70 publications
12
76
0
Order By: Relevance
“…These results indicate that in the ER, the Kit-PI3K complex is unable to activate Akt. On the other hand, STAT5 phosphorylation was enhanced by M-COPA treatment (Fig 3A and 3B), supporting our previous finding that Kit mut activates STAT5 on the ER in neoplastic mast cells [29]. Similar results were obtained with RCM cells treated with a well-known ER-to-Golgi trafficking inhibitor brefeldin A (BFA) (S3A–S3C Fig), indicating that through blocking ER export of Kit mut , M-COPA inhibits and enhances the activation of Akt and of STAT5, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results indicate that in the ER, the Kit-PI3K complex is unable to activate Akt. On the other hand, STAT5 phosphorylation was enhanced by M-COPA treatment (Fig 3A and 3B), supporting our previous finding that Kit mut activates STAT5 on the ER in neoplastic mast cells [29]. Similar results were obtained with RCM cells treated with a well-known ER-to-Golgi trafficking inhibitor brefeldin A (BFA) (S3A–S3C Fig), indicating that through blocking ER export of Kit mut , M-COPA inhibits and enhances the activation of Akt and of STAT5, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, we investigated the effect of M-COPA on oncogenic Kit signalling in neoplastic mast cells. Immunofluorescence confocal microscopic analysis showed that in RCM and HMC-1.2, Kit co-localized with the endolysosome marker cathepsin D (Fig 2A and S2A Fig), as previously described [29]. M-COPA decreased the endolysosomal localization of Kit in a dose-dependent manner (Fig 2B and S2B Fig).…”
Section: Resultssupporting
confidence: 84%
“…Our data suggest that aberrant trafficking of aggregated FcεRI in cells with Gal3 KD is accompanied by enhanced FcεRI-mediated signaling. Consistent with these findings, it has been shown that intracellular-trafficking pathways of plasma membrane receptors can determine the outcome of receptor signaling (62)(63)(64). In this connection it should be noted that we observed enhanced F-actin depolymerization in FcεRI-activated BMMCs with Gal3 KD compared to controls.…”
Section: Discussionsupporting
confidence: 78%
“…The effect of mislocalization of mutant RNF43 in the regulation of Wnt signaling pathways has not been fully elucidated. However, it has recently been reported that an aberrant localization of the receptor protein kit in the ER leads to the activation of oncogenic downstream signaling due to abnormal trafficking originating from its missense mutation, and the mechanism shown in that report may be similar to the mechanism of activation of Wnt/␤-catenin signaling by RNF43 mutants (45).…”
Section: Discussionmentioning
confidence: 80%